Fostering preservice teacher agency in 21st century writing instruction. Issue 3 (14th October 2019) - Jensen, Amber
Abstract : Purpose: This paper aims to recommend that English educators engage preservice teachers (PSTs) in thinking and acting agentively in twenty-first century writing instruction by prompting them to examine and (re)construct discourses around identity, beliefs and teaching contexts. It explores metacognitive interventions that supported one PST to assume agency to implement twenty-first century writing pedagogies that challenged institutional and curricular norms. Design/methodology/approach: A case study design was used to explore how one PST enacted agency in teaching twenty-first century writing during student teaching. Data were collected from five stimulated recall interviews that prompted metacognition over a four-month internship semester. Emerging themes were analyzed using content analysis. Findings: During interviews, the PST constructed narratives about herself, her beliefs and her teaching context in ways that catalyzed her agency to enact twenty-first century writing pedagogies in planning for instruction, framing learning with her students and negotiating with her colleagues. The PST perceived metacognitive intervention as a supportive framework for activating her agency to both "see" and "sell" (Nowacek, 2011) possibilities for implementing twenty-first century writing instruction in her first teaching context. Originality/value: While most existing literature on teacher agency focuses on practicing teachers, this paper focuses on activating agency during teacher preparation. It draws upon theories of regulative discourse (Mills, 2015), transfer (Nowacek, 2011) and metacognition as constructs for agency to identify how English educators can prepare PSTs as agents for change.